Patent Application: Educational Technologies for Enhancing and Assessing Learning - Mishra, Anjay Kumar (Apex Journal of Business and Management, 2025)
The editorial aims to enhance patent application practice among academician by illustrating content structure based on a published Indian patent with application number 202441080796 dated on 01/11/2024 on name of Dr. Shanthi P., Dr. Anjay Kumar Mishra, Dr. Manish Maheshwari, Ms. Priyanka Saxena, Dr. Debashis Mandal, Mrs. V. Suguna, Mr. S. Prakash, Saranya S., Dr. Lila Simon, Dr. B. Shoba, Ms. Deepa. N. and Dr. D. Bhuvaneswari could be verified from Office of the Controller General of Patents, Designs & Trade Marks, Government of India. Design and Educational technologies (EdTech) have transformed learning, offering innovative ways to enhance student outcomes. Online platforms provide flexible access to materials, discussions, and assessments, catering to diverse learning styles and increasing motivation. EdTech's engaging features, like gamification and virtual reality, improve understanding, critical thinking, and problem-solving skills. Assessment tools offer efficient evaluations and personalized feedback, improving learning results. E-learning platforms ensure learning accessibility, while multimedia tools make learning immersive and personalized. Online assessments give instant feedback, and data analytics help teachers adapt strategies. EdTech's continuous innovation promises to shape the future of education, making learning more effective and engaging.